18F-FDG PET in sarcoidosis: an observational study in 12 patients with infliximab - Keijsers, R.G.M.; Verzijlbergen, J.F.; van Diepen, et al., D.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
Background: 18F-FDG PET is a promising technique in sarcoidosis imaging, although it is not incorporated in routine activity assessment. The purpose of this study was to correlate 18F-FDG PET with standard sarcoidosis activity parameters during infliximab treatment. Methods: Twelve patients with refractory sarcoidosis were treated with 6 cycles of infliximab. Pre- and post-therapy 18F-FDG PET was visually evaluated and SUVmax was measured. In addition, the effect of infliximab was evaluated by changes in symptoms, angiotensin converting enzyme (ACE), soluble interleukin-2 receptor (sIL-2R), vital capacity (VC), diffusion capacity of the lung for carbon monoxide (DLCO) and chest radiography. SUVmax and conventional parameters were correlated. Results: Clinical improvement as judged by conventional parameters was seen in all patients, though with a minor response in one. Symptoms improved in 11/12 patients while chest radiographic stages did not change. The decrease in ACE was 39% and in sIL-2R 47% (p